Analisis Maslahah Najmuddin al-Thufi Terhadap Menajemen Menghadapi Tekanan Pertanyaan 'Kapan Menikah': Najmuddin al-Thufi's Maslahah Analysis of Managing the Pressure of the Question 'When to Marry' - Sugitanata, Arif; Intan Hidayah (ISTIDLAL, 2024)
This research focuses on the social and cultural dynamics related to the pressure of the question "When to get married?" which often arises in social contexts and becomes a source of psychological pressure for individuals. Using a literature study and qualitative research type and analysis based on Najmuddin al-Thufi's Maslahah theory, this research explores how to manage the pressure of the question "When to get married?". The results show that, in dealing with the question of when to get married, individuals must develop an understanding of themselves and recognise the values and goals that guide their life decisions, including in terms of marriage. It is also essential to have open dialogue and education in society to respect and understand the diverse experiences and achievements of individuals, which are not only judged by significant events such as marriage. Based on Najmuddin al-Thufi's Maslahah theory, decisions should be evaluated by considering the benefits to individuals and society. This concept underscores the importance of recognising the uniqueness of each person's journey through life and making marriage decisions based on personal readiness and desire rather than external pressures or social norms. Addressing the question of when to get married requires self-awareness and social understanding. Through education, open dialogue about different life paths, and respect for personal decisions, an inclusive and supportive society can be formed. Najmuddin al-Thufi's Maslahah theory provides a framework for processing and responding to these social dynamics with the ultimate goal of achieving individual and societal well-being.